Essential oils and oleoresins : a study of selected producers and major markets (ITC UNCTAD/GATT GenevaCH, 1986)
Study of supply position of selected major producers of, and trends in major markets for essential oils and spice oleoresins. Describes origins, uses, production and main markets for over 50 products. Contains brief descriptions of the essential oils and spice oleoresin industries in 18 producing countries. Presents the main trends in demand in USA, Canada, Western Europe and Japan. Reviews trade structures and practices. Appendices provide statistical data and listing of importers, dealers, merchants, and processing and compounding houses.
IDS